Blink: Characteristics, Controls, and Relation to Dry Eyes. (2nd January 2018) - Rodriguez, John D.; Lane, Keith J.; Ousler, George W.; Angjeli, Endri; Smith, Lisa M.; Abelson, Mark B.
ABSTRACT: Blink is a complex phenomenon that is profoundly affected by diverse endogenous and exogenous stimuli. It has been studied in the context of cognition, emotional, and psychological states, as an indicator of fatigue and sleepiness, particularly in the automobile and transportation industry, in visual tasking, and finally, as it relates to tear film stability and ocular surface health. The fact that it is highly variable and has input from so many sources makes it very difficult to study. In the present review, the behavior of blink in many of these systems is discussed, ultimately returning in each instance to a discussion of how these factors affect blink in the context of dry eyes. Blink is important to ocular surface health and to an individual's optimal functioning and quality of life. Disturbances in blink, as cause or effect, result in a breakdown of tear film stability, optical clarity, and visual function.